Patient Perceptions of Receiving COVID-19 Test Results via an Online Patient Portal: An Open Results Survey - Turer, Robert W.; DesRoches, Catherine M.; Salmi, Liz; Helmer, Tara; Rosenbloom, S Trent (Applied Clinical Informatics, 2021)
Background In the United States, attention has been focused on “open notes” and “open results” since the Office of the National Coordinator for Health Information Technology implemented the 21st Century Cures Act Final Rule on information blocking. Open notes is an established best practice, but open results remains controversial, especially for diseases associated with stigma, morbidity, and mortality. Coronavirus disease 2019 (COVID-19) is associated with all three of these effects and represents an ideal disease for the study of open results for sensitive test results.Objectives This study evaluates patient perspectives related to receiving COVID-19 test results via an online patient portal prior to discussion with a clinician.Methods We surveyed adults who underwent COVID-19 testing between March 1, 2020 and October 21, 2020 who agreed to be directly contacted about COVID-19-related research about their perspectives on receiving test results via a patient portal. We evaluated user roles (i.e., patient vs. care partner), demographic information, ease of use, impact of immediate release, notification of results, impact of viewing results on health management, and importance of sharing results with others.Results Users were mostly patients themselves. Users found the portal easy to use but expressed mixed preferences about the means of notification of result availability (e.g., email, text, or phone call). Users found immediate access to results useful for managing their health, employment, and family/childcare. Many users shared their results and encouraged others to get tested. Our cohort consisted mostly of non-Hispanic white, highly educated, English-speaking patients.Conclusion Overall, patients found open results useful for COVID-19 testing and few expressed increased worries from receiving their results via the patient portal. The demographics of our cohort highlight the need for further research in patient portal equity in the age of open results.
Keywords: patient portals; patient access to EHI; electronic health record; open results